Impact of strenuous exercise on the release of cardiac biomarkers - Le Goff, C.; Melon, P.; Kaux, J. F.; Fillet, M.; Chapelle, J. P. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Background: Cardiac troponins (cTn) are considered as the best biomarkers for detection of myocardial cell injury and NT-proBNP as the best for the cardiac insufficiency. In this study, cTnT was measured by new commercially available high-sensitive methods in subjects undergoing the Maasmarathon. Our aim was to compare cTnT and NT-proBNP levels in sportive subjects before and after a strenuous exercise. Materials and Methods: Twenty eight subjects (26 male, 42.5+-11yo) underwent a race of 42.195 kilometers between Vise (Belgium) and Maastricht (The Netherlands). We drowned blood samples before (T0), just after (T1) and three hours after the race (T3). For all patients, cTnT concentrations were measured by high sensitive methods (hsTnT, Roche Diagnostics) on heparin plasma. The NT-proBNP was also determined with the kit Roche on heparin plasma. The protocol was approved by the ethics committee of the University of Liege (Belgium). All subjects gave their informed consent. All statistical analyses were performed using Medcalc version 8.1 for Windows. pvalue <0.01 was regarded as statistically significant. Results and discussion: A significant difference between hsTnT concentrations at T0 and T1 (p<0.0001) was measured as well as between T0 and T3 (p<0.001) for NT-proBNP, but not between T1 and T3. This observation appeared only after a strenuous exercise but today this type of exercise is not reproduce easier in a laboratory of sport. Moreover, at this moment, nobody knows if these observations would have cardiac consequences at long terms. Conclusions: Measurement of cardiac troponins by high sensitive methods allows detecting significant release of biomarkers from the heart during exercise. The levels of NTproBNP were found significantly increased but in less extent than TnThs. We think that the TnThs could be an interesting marker in the future to help sport medicine to detect risk of developing a cardiac problem.